Influence of Polyvinylpyrrolidone K30 on The Complexation of Tetrahydrocurcumin with Hydroxypropyl β-Cyclodextrin - Thongyai, Srikanya; Kaewnopparat, Nattha; Songkro, Sarunyoo (Naresuan University Journal: Science and Technology (NUJST); Vol 24 No 2 (2016): May-August 2016, 2016)
Tetrahydrocurcumin (THC) is a polyphenolic compound which exhibits strong antioxidant and tyrosinase inhibition activities.  The use of THC in cosmetic or pharmaceutical formulations is limited because THC is slightly soluble in water.  Ternary complexes consist of drug-cyclodextrin and polymer as ternary component can enhance drug solubility. The objective of this present study was to evaluate the potential synergistic effect of a ternary component, polyvinylpyrrolidone K30 (PVP K30), on the solubility and physicochemical properties of THC-hydroxypropyl β-cyclodextrin (HPβCD) inclusion complex. Phase solubility analysis was used to investigate the interaction of THC in both binary (THC-HPβCD) and ternary systems (THC-HPβCD-PVP K30). The phase solubility curves were classified as A L -type with indicated a stoichiometry of 1:1 molar ratio between THC and HPβCD. By adding the PVP K30 (ternary system), the stability constant was enhanced. The binary and ternary inclusion complexes in 1:1 molar ratio were prepared by kneading and coevaporation methods. The solubility of THC from both systems was determined and the physicochemical properties were characterized by Fourier transform infrared spectroscopy (FTIR), differential scanning calorimetry (DSC) and powder X-ray diffractometry (PXRD) compared with pure THC and their corresponding physical mixtures. The results revealed that the solubility of THC in ternary systems was significantly greater than binary complexes, physical mixtures and pure THC. Ternary inclusion complex prepared by coevaporation method was found to be most effective in increasing the THC solubility. From FTIR, DSC and PXRD studies, the binary and ternary coevaporated samples gave THC in amorphous state and stronger complex formation than that of kneaded samples and physical mixtures. Keywords : Tetrahydrocurcumin, Hydroxypropyl β-cyclodextrin, polyvinylpyrrolidone K30, Complexation, Solubility
Keywords: Tetrahydrocurcumin, Hydroxypropyl β-cyclodextrin, polyvinylpyrrolidone K30, Complexation, Solubility